Traditional use of the genus Renealmia and Renealmia alpinia (Rottb.) Maas (Zingiberaceae)-a review in the treatment of snakebites (2014)
ABSTRACT: Renealmia alpinia (R. alpinia) typically occurs in the tropical rainforests of Mexico to Peru, Brazil through the Antilles, Guyana, Suriname, Colombia and Venezuela. It has traditionally been used against snakebite in Colombia. In addition to the common local use for pain, R. alpinia has been used as an antipyretic and antiemetic to treat wounds, malignant ulcers, epilepsy and fungal infections. The species of the Zingiberaceae family are famous for their use as spices and herbs. This review provides information on the traditional use of plants in the Zingiberaceae family, Renealmia genus, and specifically R. alpinia. We conducted a narrative review in English and Spanish in electronic databases, such as ScienceDirect, Napralert, PubMed, ScFinder, SciElo, during August 2011 to March 2013. We were interested in their applications in ethnomedicine and their chemical components, providing a major and methodical revision. We found 120 sources, 98 of which were selected as they contained essential information. This study has stimulated the development of a new work, which aims to isolate and evaluate metabolites from R. alpinia leads toward the development of a phytotherapeutic product, which might be accessible to the population. Studies on the toxicity and safety of R. alpinia are insufficient to provide information on the ethnomedical use of this species. Thus, the present review summarizes information about R. alpinia and proposes possible scope of future research to fill gaps identified in this narrative review.